New Zealand : Financial Sector Assessment Program: Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2017)
This paper presents an assessment of the stability of the financial system in New Zealand. Imbalances in the housing market, banks' concentrated exposures to the dairy sector, and their high reliance on wholesale offshore funding are the key macro-financial vulnerabilities. The banking sector has significant exposure to real estate and agriculture, is relatively dependent on foreign funding, and is dominated by four Australian subsidiaries. A sharp decline in the real estate market, a reversal of the recent recovery in dairy prices, deterioration in global economic conditions, and tightening in financial markets would adversely impact the system. Despite these vulnerabilities, the banking system is resilient to severe shocks. Strengthening the macroprudential framework is important.